ANALISIS PEMBELAJARAN TEMATIK PADA SISWA TUNAGRAHITA DI SLBN 1 YOGYAKARTA - Nur Rohman; Ahmad Tarmizi Hasibuan (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
The purpose of this study is to explore how the process of implementing thematic learning at SLBN 1 Yogyakarta which includes methods, strategies, techniques and the learning evaluation process. In this paper, researchers use a qualitative descriptive approach with components in the form of observation, interviews and documentation which then the collected data is then analyzed before a conclusion is drawn. The results of the research obtained are as follows: first, the method used in thematic learning at SLBN 1 Yogyakarta is a direct learning method in the form of teachers teaching material directly to students. Second, the strategy used is a drill strategy in the form of providing activities and exercises repeatedly with the aim of honing the ability of students. Third, the techniques used by teachers in the application of thematic learning to children with intellectual disabilities are thematic by providing rewards and punishments that are in accordance with the needs of students. Fourth, in the thematic learning evaluation process, schools look more at the improvements achieved by students. If there is no improvement, the school will still raise students in the next even though the learning to be delivered remains in the previous class.